Pop Culture Protest Symbol: Raising the "One Piece" Flag in Non-Violent Political Expression in Indonesia - Fathiya, Dina Nurul (International Journal of Social Research, 2025)
The phenomenon of waving the Jolly Roger flag from the anime One Piece during non-violent protests in Indonesia marks a crossroads between global popular culture and domestic political expression. This symbol is not only understood as a form of criticism of the government, but also as an expression of love for the homeland that chooses a symbolic path over physical confrontation, quickly spreading through social media and international coverage. This study aims to map the socio-political meaning of the One Piece flag in Indonesian protests, assess the relationship between pop culture symbols, authorities' responses, and public perceptions of the legitimacy of non-violent protests, and determine the effectiveness of political communication policies in the digital era. The research method uses a qualitative approach with a case study design, including semiotic analysis, critical discourse analysis, in-depth interviews, and digital netnography of social media content and international news. The results show that the One Piece flag functions as an alternative political communication medium rich in connotative meaning, sparking solidarity among the younger generation, and creating a collective imagination about the struggle against injustice. Digital virality through hashtags and political memes strengthens the resonance of this symbol, while opening up a space for transnational solidarity. Popular cultural symbols have proven to be an effective strategy for nonviolent political participation, while also challenging the state to be more inclusive in responding to the creative political practices of the younger generation. These findings contribute to the literature on pop culture politics, nonviolent political communication, and balanced digital democracy policies.